PEMBELAJARAN JARAK JAUH (PJJ) MELALUI APLIKASI GOOGLE CLASSROOM DI KELAS VII.2 SMP NEGERI 3 LUBUK LINGGAU - Merry Santi (Lentera Sriwijaya : Jurnal Ilmiah Pendidikan Matematika, 2021)
This study aims: to determine whether distance learning (PJJ) through the google classroom application can improve mathematics learning outcomes. In class VII.2 of SMP Negeri 3 Lubuklinggau, the research method used a questionnaire to collect observational data on the learning process in the form of teacher activities and activities. students at each stage of learning. For more details in obtaining these data, researchers used test techniques, observation techniques, and documentation techniques. In the first cycle, it can be seen that the average test (x1) is 75.31, 23 students complete the study, with the percentage of learning completeness is 71.88. In cycle II, it can be seen that the average test (x2) is 80.75, students who complete 28 people, with the percentage of learning completeness 87.50. The mean (x1) and (x2) increased by 5.44. The percentage of completeness learning (x1) and (x2) was 15.62%. So based on the results of the study it can be concluded that the use of the google classroom application can improve learning outcomes.